Modeling tabular icebergs submerged in the ocean. (17th August 2017) - Stern, A. A.; Adcroft, A.; Sergienko, O.; Marques, G.
Abstract: Large tabular icebergs calved from Antarctic ice shelves have long lifetimes (due to their large size), during which they drift across large distances, altering ambient ocean circulation, bottom‐water formation, sea‐ice formation, and biological primary productivity in the icebergs' vicinity. However, despite their importance, the current generation of ocean circulation models usually do not represent large tabular icebergs. In this study, we develop a novel framework to model large tabular icebergs submerged in the ocean. In this framework, tabular icebergs are represented by pressure‐exerting Lagrangian elements that drift in the ocean. The elements are held together and interact with each other via bonds. A breaking of these bonds allows the model to emulate calving events (i.e., detachment of a tabular iceberg from an ice shelf) and tabular icebergs breaking up into smaller pieces. Idealized simulations of a calving tabular iceberg, its drift, and its breakup demonstrate capabilities of the developed framework. Plain Language Summary: Large tabular icebergs break away from ice shelves around Antarctica, and drift into the ocean. As the icebergs move, they melt, which injects freshwater into the ocean. This freshwater can promote sea‐ice growth, affect deep‐water formation and alter ocean temperatures and salinities. In this way icebergs play an important part in the climate system, and need to be modeled accurately. However, the current generation of iceberg models is unable to model large tabular icebergs.In this paper, we develop a new model which can simulate the movement of large tabular icebergs drifting in the ocean. Most previous iceberg models treat iceberg as point particles which do not occupy any physical space. In our model, we represent iceberg using element which do occupy physical space, and can interact with the ocean and other elements more realistically. We then create large tabular icebergs by bonding together many smaller elements to form large structures. This allows us to simulate the movement of larger tabular icebergs in the ocean. An advantage of this approach is that by breaking the bonds between elements, we can simulate an iceberg calving away from an ice shelf, or an iceberg breaking into two or more parts. Key Points: A novel modeling framework is developed to explicitly model large tabular icebergs submerged in the ocean Tabular icebergs are represented using Lagrangian elements that drift in the ocean, and are held together by numerical bonds Breaking the numerical bonds allows us to model iceberg breakup and calving